Recent expansion of Daphnia across Beringia, 2001-2011 - Derek Taylor (Arctic Data Center, 2017)
Daphnia pulex is quickly becoming an attractive model species in the field of ecological genomics due to the recent release of its complete genome sequence, a wide variety of new genomic resources, and a rich history of ecological data. Sequences of the mitochondrial NADH dehydrogenase subunit 5 and cytochrome c oxidase subunit 1 genes were used to assess the global phylogeography of this species, and to further elucidate its phylogenetic relationship to other members of the Daphnia pulex species complex. Using both newly acquired and previously published data, we analyzed 398 individuals from collections spanning five continents. Eleven strongly supported lineages were found within the D. pulex complex, and one lineage in particular, panarctic D. pulex, has very little phylogeographical structure and a near worldwide distribution. Mismatch distribution, haplotype network, and population genetic analyses are compatible with a North American origin for this lineage and subsequent spatial expansion in the Late Pleistocene. In addition, our analyses suggest that dispersal between North and South America of this and other species in the D. pulex complex has occurred multiple times, and is predominantly from north to south. Our results provide additional support for the evolutionary relationships of the eleven main mitochondrial lineages of the D. pulex complex. We found that the well-studied panarctic D. pulex is present on every continent except Australia and Antarctica. Despite being geographically very widespread, there is a lack of strong regionalism in the mitochondrial genomes of panarctic D. pulex ‐ a pattern that differs from that of most studied cladocerans. Moreover, our analyses suggest recent expansion of the panarctic D. pulex lineage across continents with some continents sharing identical haplotypes. The hypothesis that hybrid asexuality has contributed to the recent and unusual geographic expansion of the panarctic D. pulex lineage warrants further study.